PERANCANGAN SISTEM PEMANAS AIR MENGGUNAKAN SISTEM KENDALI PID - I.W. Parmadi Putra; I. W. Arta Wijaya; I.N. Budiastra (Program Studi Teknik Elektro UNUD, 2020)
As the technology advances in control system grow rapidly, especially those involved with water temperature, there is anincreased demand for a control system that is able to provide precisely stable temperature value. The commonly used systemsnowadays are still using the ON/OFF control system for it is relatively affordable and simple, but unfortunately numerouserrors are still found and it is not yet able to provide precise data. Therefore, a PID control system was developed to addressthis issue. In this study, Arduino UNO temperature control was used as data acquisition system, and LM35 temperature sensorwas used to detect the temperature recognized by signal conditioning. From the signal conditioning, the driver will then controlthe heater in order to obtain a precise temperature. This PID system utilized a water-resistant temperature sensor. In this study, the heater was treated by means of controlling the PID temperature which ranged from 69oC to 70.5oC. Another test was doneby comparing the temperature value detected by the device’s temperature sensor with an external digital thermometer whichwas placed in the same container. The temperature value detected by the device’s temperature sensor had a difference of ±1,300C compared to the digital thermometer.